2017
DOI: 10.1111/cpf.12493
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT to detect adverse reactions to metal debris in patients with metal‐on‐metal hip arthroplasty: an exploratory prospective study

Abstract: adverse reactions to metal debris; hip arthroplasty; magnetic resonance imaging; metal-on-metal hip prosthesis; PET/CT Metal-on-metal (MoM) bearings in total hip arthroplasties and hip resurfacing arthroplasties have recently shown a new type of complication: adverse reactions to metal debris (ARMD). ARMD is characterized by local severe inflammation and tissue necrosis leading to implant failures. The gluteal muscle region is important for the patient outcome after revision surgery. This prospective positron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We cannot exclude that this definition might have contributed to the high sensitivity and low specificity of 18 F-FDG PET/CT observed in the current study. It should be also kept in mind that adverse reactions to metal debris can result in an increased 18 F-FDG uptake that is indistinguishable from that occurring at foci of infection [14]. In a previous study that used similar criteria for positive findings, the sensitivity and specificity for infected hip arthroplasties were 100% and 44.8%, respectively [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot exclude that this definition might have contributed to the high sensitivity and low specificity of 18 F-FDG PET/CT observed in the current study. It should be also kept in mind that adverse reactions to metal debris can result in an increased 18 F-FDG uptake that is indistinguishable from that occurring at foci of infection [14]. In a previous study that used similar criteria for positive findings, the sensitivity and specificity for infected hip arthroplasties were 100% and 44.8%, respectively [15].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, preliminary data on the potential usefulness of 68 Ga-citrate PET for identifying patients with bone infections have been promising [13]. In a head-to-head comparison, 18 F-FDG PET/CT has been superior to 68 Ga-citrate PET/CT for diagnosing inflammatory reactions elicited by metal debris [14]. However, the question as to whether 68 Ga-citrate PET/CT is either superior or may offer complimentary information to 18 F-FDG PET/CT in detecting lower limb prosthesis infections remains open.…”
Section: Introductionmentioning
confidence: 99%
“…In Mycobacterium tuberculosis, 68 Ga citrate showed better lesion detection of intracranial lesions, due to the absence of tracer accumulation in the brain [62]. Moreover, studies have suggested 68 Ga citrate is less likely to accumulate in post-infective lesions after treatment of the different infections [62][63][64]. Large multi-centred prospective studies are needed to investigate the use of 68 Ga citrate in fungi for these indications.…”
Section: Pet Labelled Antifungal Agentsmentioning
confidence: 99%
“…Despite this, our study showed that 68 Ga-citrate-PET/CT detected abnormal tracer uptake in all the patients who had TB. Another study evaluated the characteristics of 18 F-FDG and 68 Ga-citrate PET/CT in a condition characterized by a severe inflammatory process with necrosis due to the reaction to metal debris in patients with metal on metal hip arthroplasties [25]. 18 F-FDG PET/CT showed periprosthetic uptake in 94 % (15/16) of hip arthroplasties with 68 Ga-citrate showing periprosthetic uptake in only 19 % (3/16).…”
Section: ▶Fig 3 a 18 F-fdg And B 68mentioning
confidence: 99%